La Coherencia de Políticas para el Desarrollo en los ámbitos subestatales. Reflexiones a la luz del caso del País Vasco - Unceta, K.; Labaien, I. (Revista Iberoamericana de Estudios de Desarrollo)
The debate on Policy Coherence for Development (PCD) has mostly been associated to States. However, the growing importance acquired by local and regional governments in promoting development and cooperation policies, and the need of a multilevel governance to meet the challenges of development, emphasize the interest of analysing the PCD from a wider perspective including the sub-state level. Considering these issues, this paper focuses on the study of the PCD in the Basque Country, based on a research study carried out about this subject. As a conclusion, relevant considerations that may be interesting to promote the analysis on PCD at sub-state level are pointed out.